2011
DOI: 10.1002/stem.752
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Analysis of Molecular Pathways Underlying Induced Pluripotent Stem Cell Induction

Abstract: Induced pluripotent stem cells (iPSCs) can be reprogrammed from adult somatic cells by transduction with Oct4, Sox2, Klf4, and c-Myc, but the molecular cascades initiated by these factors remain poorly understood. Impeding their elucidation is the stochastic nature of the iPS induction process, which results in heterogeneous cell populations. Here we have synchronized the reprogramming process by a two-phase induction: an initial stable intermediate phase following transduction with Oct4, Klf4, and c-Myc, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(87 reference statements)
1
10
0
Order By: Relevance
“…These substitutes may be useful in future studies in non-mammalian species. A recent study also showed that an intermediate state of stem cell induction can exist, by using just a few of the transcription factors (Lin et al, 2011). Different from our iPSC-like cells they did not successfully achieve pluripotency in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These substitutes may be useful in future studies in non-mammalian species. A recent study also showed that an intermediate state of stem cell induction can exist, by using just a few of the transcription factors (Lin et al, 2011). Different from our iPSC-like cells they did not successfully achieve pluripotency in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…After verifying the expression levels of a subset of candidate genes by RT-qPCR, we identified Zfp459 , Zfp819 and Zfp936 as specifically expressed in pluripotent cells. Supporting a link between Zfp459 , Zfp819 and pluripotency, two recent reports demonstrated that expression of Zfp459 is induced during the late stages of reprogramming MEFs into induced pluripotent stem cells (iPSCs) [65], and that the promoter of Zfp819 is bound by OCT4, KLF4 and SOX2 between a pre-iPSC stage and fully reprogrammed iPSCs [66]. Interestingly, when we sought potential transcriptional regulators of these three pluripotency-associated KRAB-ZFP genes using publicly available ChIP-seq data, we noticed that the genomic regions encompassing Zfp459 and Zfp819 gene bodies and flanking sequences were enriched in binding sites for TFs belonging to the core pluripotency network, and that this phenomenon was specific for these two genes compared to other transcription units contained in the same genomic clusters.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that although low Sox2 expression may repress ectoderm and mesoderm markers, the other RTFs are also involved in the repression of ectoderm and mesoderm marker genes. Furthermore, it has been proposed that a two-step reprogramming mechanism is necessary for the induction of pluripotency, and that Sox2 functions in the latter stages of reprogramming (26). Our data and a previous report suggest that Sox2 expression levels are low during the early phase of reprogramming (25).…”
Section: Discussionmentioning
confidence: 99%